Penampilan Reproduksi Induk Kambing Kacang di Kecamatan Galang Kabupaten Tolitoli - Artati, Artati; Muliana, Muliana (Fakultas Peternakan Universitas Madako Tolitoli, 2025)
This study aimed to describe the reproductive performance of Kacang does raised by smallholder farmers in Galang District, Tolitoli Regency. The research employed a descriptive quantitative method through field observations and structured interviews with 44 farmers representing a total of 332 Kacang goats. The observed variables included age at first mating, postpartum mating interval, kidding interval, litter size, and pre-weaning mortality. Data were analyzed descriptively by calculating the mean, frequency, and percentage for each parameter and were compared with previous studies. The results showed that the average age at first mating ranged from 6 to 12 months, postpartum mating interval was 2–4 months, kidding interval was 7–9 months, litter size was 1–2 kids per birth, and pre-weaning mortality was 9.09%. These findings indicate that Kacang does in Galang District exhibit good reproductive efficiency and adaptability to tropical conditions. The main contributing factors are the availability of natural forage throughout the year, farmers’ experience, and stable traditional management practices. However, the low educational level of farmers and the lack of reproductive record-keeping remain limiting factors that need to be addressed through improved management and targeted extension programs